Luo Yin’s Travel-Style Poetry of the Late Tang Dynasty - Liew, Sui Mee (2019)
This research discussed Luo Yin's Travel-Style Poetry of the Late Tang Dynasty. The decline of the political power in the Late Tang Dynasty led to the waning of poetry during the time as well. Nevertheless, there were still many poets who wrote a significant amount of poems adding to the wealth of literature during the Late Tang Dynasty. One of these poets was Luo Yin (AD 833-909) who was an eminent poet then. He had written approximately 500 poems which were unique in style, artistic in characteristics and high in research values. Unfortunately, his work did not garner the attention of his contemporary and the many subsequent later generations. In the recent decades, Luo Yin's poems gradually caught the attention and interests of researchers. However, much scopes were left to be further explored and researched on his poems especially his Travel-Style Poetry which had made significant contributions during the Late Tang Dynasty. His Travel-Style Poetry was written while he was travelling, drifting from place to place, away from the comfort of his home. The poems were rich in historical and cultural values and depicted his philosophical thoughts. The research defined and analysed Luo Yin's Travel-Style Poetry. It systematically categorised and analysed with statistics and tables, the content, genre, year and place of the poems written in Luo Yin's Travel-Style Poetry and his travel life. At the same time, the research combined relevant literature and information and made further analysis and exploration. The research also supplemented Li Dingguang's work of compiling Luo Yin's Travel-Style Poetry with the year written for some of the poems in the collection. The research concluded that Luo Yin's Travel-Style Poetry contained multi characteristics and unique artistic style, fully reflected the thoughts and experiences of the author's travel life, his philosophical thinking and unabated fighting spirits. Thus, the research affirmed the contributions and achievements of Luo Yin to the Travel-Style Poetry of the Late Tang Dynasty.